Posthumanism and Latin(x) American Science Fiction
XIII, 257 p. 2 illus.
Keywords: This volume explores how Latin American and Latinx creators have engaged science fiction to explore posthumanist thought. Contributors reflect on how Latin American and Latinx speculative art conceptualizes the operations of other, non-human forms of agency, and engages in environmentalist theory in ways that are estranging and open to new forms of species companionship. Essays cover literature, film, TV shows, and music, grouped in three sections: “Posthumanist Subjects” examines Latin(x) American iterations of some of the most common figurations of the posthuman, such as the cyborg and virtual environments and selves; “Slow Violence and Environmental Threats” understands that posthumanist meditations in the hemisphere take place in a material and cultural context shaped by the catastrophic destruction of the environment; the chapters in “Posthumanist Others” shows how the reimagination of the self and the world that posthumanism offers may be an opportunity to break the hold that oppressive systems have over the ways in which societies are constructed and governed. Antonio Córdoba is Associate Professor of Modern Languages and Literatures at Manhattan College, USA. His main area of specialization is Latin American and Iberian science fiction. He has published ¿Extranjero en tierra extraña?: El género de la ciencia ficción en América Latina (2011) and published articles and book chapters on Latin American and Spanish science fiction and horror. Emily A. Maguire is Associate Professor of Spanish and Portuguese at Northwestern University, USA, where she specializes in literature of the Hispanic Caribbean and its diasporas. The author of Racial Experiments in Cuban Literature and Ethnography (2011; 2nd edition, 2018), her articles have appeared in Revista de Estudios Hispánicos, Small Axe, A Contracorriente, ASAP/Journal, and Revista Iberoamericana, among other places.